2019
DOI: 10.1136/archdischild-2019-317080
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural outcome in twin–twin transfusion syndrome survivors treated with laser surgery

Abstract: ObjectiveEvaluate the incidence of and risk factors for behavioural problems in twin–twin transfusion syndrome (TTTS) survivors treated with fetoscopic laser coagulation.DesignObservational cohort study.SettingNational referral center for fetal therapy, Leiden University Medical Center, The Netherlands.PatientsBehavioural outcome was assessed in 417 TTTS survivors, at the age of 2 years.InterventionsParents completed the Child Behavior Checklist for their twins. Antenatal, neonatal and follow-up data including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A previous study by our center reported a similar rate of behavioral problems in survivors of TTTS as in the normal population. 27 The rate of behavioral problems in this study is consistent with these results. At a younger age, impairment can potentially remain concealed due to low test sensitivity (ie, Bayley scales vs Wechsler scales).…”
Section: Discussionsupporting
confidence: 90%
“…A previous study by our center reported a similar rate of behavioral problems in survivors of TTTS as in the normal population. 27 The rate of behavioral problems in this study is consistent with these results. At a younger age, impairment can potentially remain concealed due to low test sensitivity (ie, Bayley scales vs Wechsler scales).…”
Section: Discussionsupporting
confidence: 90%
“…In a survey of 78 pregnant mothers who had undergone laser treatment 18% of the cases developed neurologic impairment [ 11 ]. In a similar study on 332 twins, no difference was noted between the incidence of neurologic impairment in the normal population and twins with TTTS [ 12 ]. Otherwise, NDI was not different according to the TTTS stages.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53] A study showed that endoscopic laser therapy had better outcomes in overall survival, neurologic morbidity, and Laser Therapy During Pregnancy neonatal death compared with serial amnioreduction. [54][55][56][57] Behavioral problems did not increase in twins treated with laser ablation compared with the general population. 58 After fetoscopic laser surgery, complications such as placental abruption, preterm premature rupture of the membranes, persistent trophoblastic disease, and intrauterine fetal death may increase.…”
Section: Twin To Twin Transfusion Syndromementioning
confidence: 99%